Letter from Sydney Brenner to Dr. W.H. McClain - Brenner, Sydney (My University, 2017)
The suppression of lambda phage amber mutants in E. coli cells by transcripts from synthetic tRNA suppressor gene sequences derived from Archaeal cells.
Keywords: Amber mutation, suppression